Distribution strategy planning: A comprehensive probabilistic approach for unpredictable environment - Theodor Petřík (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Uncertain future development presents a significant challenge during the distribution strategy planning process. Traditional planning approaches, reliant on creating potential scenarios and assigning probabilities, often struggle due to future developments' inherent unpredictability, which can lead to suboptimal strategies if probabilities are inaccurately estimated. This paper introduces a novel method designed to navigate these uncertainties without rigid assumptions about the exact probability of each future scenario. This method aims to identify optimal strategies applicable across a wide range of situations by exploring the entire allowable probability space. The effectiveness of this approach is demonstrated by a case study of a real-world Czech company considering potential expansion. The optimal distribution stratégy is formulated and evaluated in the case study for six years, considering multiple potential development scenarios.
Keywords: D81; D22; C44; C61; 330; Decision-making under uncertainty; Economic efficiency; Transport Economics; Probabilistic Approach